Gestão estratégica da informação como fator condicionante para a definição e implementação de políticas de defesa e segurança nacional no contexto da Amazônia Legal: o caso SIPAM/SIVAM - Santos, Jean Carlo Silva dos (2007)
The objective of this work is the study of the existing correlations between the strategical use of the information and the joint and implementation of defense politics and national security in the Legal Amazonian. For in such a way, the proposal was developed from the analysis of the systems of protection and monitoring of the Amazonian (SIPAM/SIVAM), where we search to inquire as these systems have contributed for the definition and implantation of these politics. For the Amazonian, with its natural wealth, threats and vulnerabilities, the perspectives of integration, security and national defense and of sustainable development constitute great challenges to be faced, where the efficient use of the technology is a basic reference that must be incorporated in the strategies and public politics in these areas. One is about a strategical project, conceived with vision of future, protection and development of the . The objective SIPAM/SIVAM the defense and the guarantee of the Brazilian sovereignty in the Legal Amazonian, beyond the systematization and accomplishment of the governmental actions in the region, by means of the intensive use of technological apparatus. In turn, they reflect the priority that the Amazon region has in terms of defense and security for the Country, and symbolize the strategy of the State to protect it. The SIPAM/SIVAM if finds in a boarding line in which the guarantee of the national sovereignty also involves the care with the development of the local population, inside of a proposal educative and integrator. Like conclusion we affirm that of the SIPAM/SIVAM creates a new paradigm for the public administration, where the organizations work with a shared set of information, beyond starting to act of integrated form. Thus, when searching permanently the rationalization of efforts and resources, trying an unknown form of institution relationship where infrastructure and products are shared, the SIPAM/SIVAM creates a new premise for the Brazilian public administration and contributes to give a new direction to the development of the Amazonian.